Prediction of landscape ecological security under different SSP-RCP scenarios in the Huaihe River Eco-Economic Belt, China - Huaijun Wang; Yifeng Sun; Yingping Pan; Ziyun Wang (Geocarto International)
The prediction of ecological security risks is crucial for advancing the sustainable development of both nature and society. Using the PLUS model, we predicted land use changes in the Huaihe River Eco-Economic Belt under five Shared Socio-economic Pathway-Representative Concentration Pathway (SSP-RCP) scenarios, and analyzed the resulting landscape patterns and their influencing factors. The results showed that: (1) From 2010 to 2020, the study area experienced significant land use changes, including a marked increase in urban and rural land and a notable decrease in cropland. Urbanization emerged as the dominant trend across all SSP-RCP scenarios, with urban and rural land continuing to expand until 2050, after which they stabilized. SSP370 presented the smallest extent of urban and rural land, while SSP585 exhibited the largest. (2) The mean patch size (Areamn), mean patch fractal dimension (Fracmn), mean shape index (Shapemn), and mean contiguity index (Contigmn) showed an increasing trend, whereas the number of patches (NP) and patch density (PD) decreased. These trends suggested an overall improvement in ecological security, with landscapes becoming less fragmented and characterized by larger, more complex, and more contiguous patches. The landscape pattern showed significant changes, with 2050 identified as a threshold year, largely influenced by urbanization trends. (3) The landscape indices indicated that SSP370 was associated with relatively less fragmentation, while SSP126 and SSP245 were associated with higher fragmentation. The proportion of urban and rural land explained the majority of the variance in landscape indices across all scenarios. This study highlighted the importance of understanding the impacts of urbanization on landscape patterns to develop effective strategies for promoting sustainable development and the conservation of both nature and society.